Big-data, a digital ocean in the Information Society - Monleon-Getino, Antonio (Historia y Comunicación Social, 2015)
Immersed in the digital revolution, we generate data consistently and most are stored. This is what has been called the Big-data. Along with capital and labor force data have become an added value to the economy that reflects a future with a revolutionary paradigm in which society will be directed by the data. The future is in research, treatment and application data that will bring prosperity to our society. In this article the rules and laws that exist today in the Big-data and existing regulations are collected. To analyze the Big-data passes through the machine learning that deals with the construction and study of algorithms that can learn from data solution. There are many techniques such as descriptive statistics, sorting or grouping. This article describes the technologies that are used to store and analyze the “Big data” is collected.